Correlation of Allergic Rhinitis Patient Questionnaire with Skin Prick Test Results at Saiful Anwar Regional Hospital - Maharani, Iriana; Kurniadi, Melody Audria (Biology, Medicine, & Natural Product Chemistry, 2025)
Objective: To determine the optimal cut-off value of the Allergic Rhinitis Patient Questionnaire as a diagnostic tool and its correlation with Skin Prick Test (SPT) results; Methods: The data used were medical records at the ENT Polyclinic dr. Saiful Anwar Hospital with cross sectional method then the data was processed with the SPSS application; Results.: Demographic data are dominated by males (56.3%) with an age range of 19-59 years (74.7%). The most common symptom complained was nasal congestion (71.3%). The trigger of symptoms is dominated by dust allergens (77%). The most common classification of Allergic Rhinitis (AR) is moderate – severe (50.6%) with Visual Analogue Scale (VAS) score > 5 and dominated by complaints of sleep disturbances (57.5%). The optimal limit value of the Allergic Rhinitis Patient Questionnaire is 10, where patients with a score value ³ 10 can be assumed to suspect AR. There is a significant correlation between the results of the assessment using the Allergic Rhinitis Patient Questionnaire and the results of the SPT examination. Conclusion: Patients with a total score of Allergic Rhinitis Patient Questionnaire ³ 10 were assumed to be suspected of AR and the results of the questionnaire assessment correlated with the SPT results.